Identification of rab2 as a tubulovesicle-membrane-associated protein in rabbit gastric parietal cells. - Tang, L H (1992)
Rab proteins, which are ras-like low-molecular-mass GTP-binding proteins, are postulated to act as specific regulators of membrane trafficking in exocytosis and endocytosis. Previously, we reported a 23 kDa tubulovesicle-associated GTP-binding protein in rabbit gastric parietal cells [Basson, Goldenring, Tang, Lewis, Padfield, Jamieson & Modlin (1991) Biochem. J. 279, 43-48]. The major component of the 23 kDa protein is now identified as rab2. Rab2 was co-localized in tubulovesicle membranes from parietal cells. Consistent with GTP-binding activity (as documented before), upon maximal stimulation of parietal cells, rab2 immunoreactivity was redistributed from a 50,000 g to a 4000 g subcellular membrane fraction. The tubulovesicle-associated rab2 behaved as an integral membrane protein, since both 0.5 M-NaCl and 0.1 M-carbonate extraction failed to remove the protein from the tubulovesicle membrane. Utilizing a PCR the rab2 cDNA sequence from rabbit parietal cells was obtained, and it showed only one amino acid difference compared with the human sequence. The results of the present study provide strong evidence that parietal cells possess a rab2 protein which is tightly associated with tubulovesicle membranes.